فاعلية النصوص الإجرائية في تحقيق الأمن القضائي خلال مرحلة التحقيق الابتدائي (دراسة تحليلية) - Salim, Kastro; Abdulkarim, Dr. Mohammed (Journal of Legal and Political Studies, 2025)
Judicial security constitutes one of the fundamentalpillars of the criminal legal system, as it ensures the protection ofdefendants rights from any arbitrariness throughout the stages of criminal proceedings, reflecting the judiciary's commitment to the principles of justice and integrity. This study focuses on evaluating the adequacy and effectiveness of the procedural provisions in the Iraqi Code of Criminal Procedure in achieving judicial security. By analyzing the provisions related to the preliminary investigation, defense rights, legal representation, witness examination, rules for evidence collection, and the presumption of innocence, the study aims to assess the effectiveness of these provisions in safeguarding defendants' rights and ensuring a fair and impartial trial. The study also examines any gaps or challenges that may affect the practical application of these provisions and compares them with international standards of judicial security. The research aims to provide recommendations to enhance legislation and judicial procedures, thereby improving the efficiency of the Iraqi judicial system in protecting defendants' rights and ensuring justice. Keywords: Judicial security, criminal law, legal security, defendants' guarantees, trial, preliminary investigation.
Keywords: Keywords Judicial security; criminal law; legal security; defendants guarantees; trial; preliminary investigation